Peningkatan Kualitas Bio-Ink dengan Penambahan Pigmen Kunyit Untuk Warna Yellow pada Printer Digital - Yuniarti, Endang; Djonaedi, Emmidia; Rudi Kusumantoro, Heribertus; Zahira Adni Shaffa, Ghaitsa; Salsabila, Salsabila (Politeknik Negeri Ketapang, 2024)
Improving the quality of bio-ink by adding turmeric pigment for yellow color on digital printers in Jakarta State Polytechnic. One of proper ink for food packaging is ink that made from organic materials. Organic/bio- ink is ink whose pigments come from natural materials or from living things such as animals and plants. In general, conventional digital printer ink is made from synthetic chemicals that contain hazardous and toxic materials (B3) and can have a negative impact on the environment. One of the organic ink dyes derived from plants is turmeric root as a yellow dye. Curcumin pigment has the potential as a raw material for organic inkjet ink because it is environmentally friendly, cheap, and locally available. The purpose of this study was to obtain the composition of turmeric ink to achieve a yellow color that is close to the standard of conventional ink. The method used is a mixing process between turmeric pigment powder, ethanol, aquades, and gum Arabic. The variations of pigments used are 18 g, 20 g and 22 g.